P70 The use of in-situ simulation to enhance education and test safety systems within an acute paediatric setting. (31st December 2017) - Semmens, Alison; Richards, S; Rees, C
Abstract : Aims: To showcase a different way of using in-situ simulation within an acute paediatric setting, to test safety systems and enhance education for the multi-disciplinary team. To share our experiences to enable you to identify where in-situ simulation can be used in your workplace. Context: In-situ simulation training has been used in our workplace for over a decade. In 2015, a new Children's Hospital for Wales opened, within this, a new hydrotherapy pool. This led to the simulation team developing scenarios, not only for education purposes, but also to test new equipment in a new setting. This was to ensure safety systems were in place, with all emergency team members aware of these systems. Wheeler et al (2013) suggest that simulation can be used to test the implementation of new protocols, to ensure their applicability and discover potential issues that may not otherwise be discovered until applied to a real patient care situation. Description: We carried out an in-situ simulation with a physiotherapist patient actor collapsing in the hydrotherapy pool. This was performed as a mock arrest scenario with all members of the crash team attending unawares. This proved to be very successful for education, situational awareness and some safety aspects. We went on to performing and recording (via media resources) an in-situ hybrid simulation. This consisted of a child patient actor collapsing in the pool. The patient actor was evacuated from the pool, resuscitated on the poolside and transferred into a nearby dry area, where resuscitation was continued on a high fidelity manikin. The episode, including debrief, was filmed and subsequently utilised for teaching and training purposes. Learning objectives: a) To ensure all members of the emergency teams became familiar with the hydrotherapy location, equipment and new safety procedures developed by hydrotherapy staff b) how to run an effective in-situ simulation, including hybrid simulation c) to identify where in-situ simulation can be used in your workplace. Discussion: This in-situ hybrid simulation allowed us to identify twelve safety and training points that needed to be addressed. As well as enhancing education from a medical perspective, we ensured safety systems were tested and subsequently modified to ensure future high quality patient care. We also provided those within the attending emergency team with thoughts to take back to their workplace of how to effectively perform simulation for safety and training purposes.